Multiple myeloma: methods and protocols - Heuck, Christoph; Weinhold, Niels (Methods in Molecular Biology, 2018)
ELDA qASO-PCR for High Sensitivity Detection of Tumor Cells in Bone Marrow and Peripheral Blood -- EuroFlow-Based Next-Generation Flow Cytometry for Detection of Circulating Tumor Cells and Minimal Residual Disease in Multiple Myeloma -- Cytoplasmic Immunoglobulin vs DNA Analysis by Flow Cytometry -- Deep Profiling of the Immune System of Multiple Myeloma Patients by Cytometry by Time of Flight (CyTOF) -- Fluorescence In Situ Hybridization (FISH) in Multiple Myeloma -- Whole Exome Sequencing in Multiple Myeloma to Identify Somatic Single Nucleotide Variants and Key Translocations Involving Immunoglobulin Loci and MYC -- RNA-Sequencing from Low-Input Material in Multiple Myeloma for Application in Clinical Routine -- Protocol for M3P: A Comprehensive and Clinical Oriented Targeted Sequencing Panel for Routine Molecular Analysis in Multiple Myeloma -- Analysis of Circulating Tumor DNA -- Detection of Cross-Sample Contamination in Multiple Myeloma Samples and Sequencing Data -- Analysis of Global Gene Expression Profiles -- Genome Wide Mapping of Methylated and Hydroxyl-Methylated Cytosines using a Modified HpaII Tiny Fragment Enrichment by Ligation Mediated PCR Tagged Sequencing Protocol -- A Rapid and Robust Protocol for Reduced Representation Bisulfite Sequencing in Multiple Myeloma -- Microfluidic Production and Application of Lipid Nanoparticles for Nucleic Acid Transfection -- Microfluidic Assembly of Liposomes with Tunable Size and Co-Loading Capabilities.